2020
DOI: 10.3390/brainsci10090629
|View full text |Cite
|
Sign up to set email alerts
|

Response to Placebo in Fragile X Syndrome Clinical Trials: An Initial Analysis

Abstract: Fragile X syndrome (FXS) is the leading cause of inherited intellectual disability and autism spectrum disorder. Individuals with FXS often present with a wide range of cognitive deficits and problem behaviors. Educational, behavioral and pharmacological interventions are used to manage these and other complex issues affecting individuals with FXS. Despite the success of preclinical models and early-phase drug clinical studies in FXS, large-scale randomized-controlled trials have failed to meet primary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…There were several limitations in the design of this study, the first being the lack of a placebo-control arm. FXS studies have been shown to have large placebo effect for behavioral measures (Berry-Kravis et al, 2018;Luu et al, 2020), with some reporting a placebo effect size similar to the OV101 effect size observed in the present study (Berry-Kravis et al, 2016;Youssef et al, 2018). Another limitation was the small sample size (n 23), which may have been insufficient to assess behavioral efficacy, as prior studies that enrolled more than 100 participants have yielded ambiguous results (Berry-Kravis et al, 2016;Berry-Kravis et al, 2018;Youssef et al, 2018;Berry-Kravis et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There were several limitations in the design of this study, the first being the lack of a placebo-control arm. FXS studies have been shown to have large placebo effect for behavioral measures (Berry-Kravis et al, 2018;Luu et al, 2020), with some reporting a placebo effect size similar to the OV101 effect size observed in the present study (Berry-Kravis et al, 2016;Youssef et al, 2018). Another limitation was the small sample size (n 23), which may have been insufficient to assess behavioral efficacy, as prior studies that enrolled more than 100 participants have yielded ambiguous results (Berry-Kravis et al, 2016;Berry-Kravis et al, 2018;Youssef et al, 2018;Berry-Kravis et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
“…The identification and evaluation of valid, sensitive-to-treatment biomarkers is increasingly necessary to reliably track treatment changes in the unfolding wave of clinical studies in FXS (Budimirovic et al, 2017;Erickson et al, 2018;Lee et al, 2018) and to substantially mitigate the large placebo effect in FXS studies. Indeed, an effort to differentiate objective from subjective improvements in individuals with FXS is recommended by experts in the field of FXS (Luu et al, 2020). For example, electroencephalography is a potential neural biomarker sensitive to treatment (Erickson et al, 2018;Ethridge et al, 2019), and molecular studies have shown a link between FMR1 expansion, gene methylation, and FMRP deficit and the overall severity of the neurobehavioral phenotype (Berry-Kravis et al, 2018;Budimirovic et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although additional studies with a larger cohort on higher doses would be required to confirm this finding, these results suggested potential dose- and age-related effects as well as a possible optimization of primary study endpoints, pointing toward a potential benefit of arbaclofen in future optimized clinical trials. Double-blind, randomized, placebo-controlled studies in FXS are also highly recommended to properly assess the sensitivity and specificity of clinical endpoints ( 63 , 72 , 73 ).…”
Section: Diversity Of Responses To Therapeutic Treatmentsmentioning
confidence: 99%
“…Most measures employed in clinical trials have been deemed moderately effective as outcome tools and there exists limited data on their sensitivity to detect pharmaceutically driven changes [ 26 ]. The majority of outcome measures involve parent/caregiver reports, which are inherently susceptible to scoring variability and placebo effects [ 127 ]. The most widely used primary outcome measure for clinical trials in FXS has been the Aberrant Behaviour Checklist- Community (ABC-C), a parent or caregiver report which assesses maladaptive behaviours as perceived in the weeks prior to rating.…”
Section: Introductionmentioning
confidence: 99%